Development of fatigue cracks from mechanically machined scratches on 2024-T351 aluminum alloy - Part 1: experimentation and fractographic analysis - Cini, Andrea; Irving, Phil E. (Wiley, 2016)
Clad and unclad 2024-T351 aluminium alloy sheets, weakened by mechanically machined scratches, were fatigued to investigate the effect of small surface damage, like scribe marks, on aircraft fuselage joints. The role of scratch cross section geometry on fatigue life of scribed components was analysed. Scratches between 25 and 185 µm deep, with 5, 25 and 50 µm root radii, were cut on sample surface by using diamond-tipped tools. After testing, fracture surfaces were examined using a scanning electron microscope, and crack growth rates were measured by striation counting. Scratches reduced aluminium fatigue life under tensile and bending load up to 97.8% due to multiple crack nucleation at their roots. Short cracks nucleated from sharp scratches coalesced to form unique elongated cracks growing through sample thickness. Cracks initiated from scratches were typical short cracks, growing faster than conventional long cracks. Despite the different scribing process, fatigue data of regular diamond tool cut scribes can be used to conservatively predict life reduction owing to ploughed in-service scribe marks on fuselage joints. Finite element analyses on scribed samples and the fatigue life prediction models are described in Part II of this paper.
Keywords: Notch fatigue; scratches and scribe marks; small cracks; fractography; striations